ON THE ISSUE OF RATIONAL ORGANIZATION OF THE TEXTILE AND KNITWEAR ENTERPRISES HEAT AND POWER SUPPLY SYSTEM - V. N. Romaniuk; D. B. Muslina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers organization of the industrial enterprise heat and power supply system (HPSS), to be rational from the structure and flow parameter standpoint. Developing HPSS is one of the main lines of implementing energy-saving potential in volumes complying with dictates of the time on reducing the production cost energy component, which is especially vital for the light industry enterprises of Belarus. To reduce the complexity of the task the authors employ the hierarchical structure of HPSS. With regard to textile and knitwear enterprises, they show the irregularity of energy supply on the one hand, and of energy use on the other. The finishing departments of the specified enterprises ensure their thermo-technological status. It is proverbial that accomplished in terms of energy thermo-technological enterprises should not consume the electric energy produced in condensation electric power plants. Instead, for their production needs, they should use thermal energy and electricity generated in the CHP. At the same time, steam turbine CHPs of low power, and consequently of low initial parameters, cannot provide the required electrical and heat energy flow generation balance. The indicated circumstance among others accounts for prevalence of condensation electric power plants in the scheme of electrogenerating capacities that provide work for the light industry enterprises. And this leads to irregularity of their energy supply. Transition to gas CHPs with required scheme of the energy flow generation is associated primarily with creation of inherent generating sources, which in its turn poses a number of challenges on modification of the thermal treatment schemes of technological flows. The problem is solved in package with developing energy consumption of the finishing department as well as the entire enterprise. The study shows the capability of utilizing low pressure hot water alongside with steam, which paves the way to the recuperative use of the secondary low-temperature heat flows – utilizing their energy by engaging lithium-bromide absorption heat pumps. The congruous development of energy utilization from the position of systems approach in the context of Belarus is the task of a higher priority than transition to cogeneration energy supply.